COMMUNICATING SPECIALIZED KNOWLEDGE old genres and new media. - Bondi, Marina (CAMBRIDGE SCHOLARS PUBLISHING, 2019)
This book was born out of the idea that domain-specific knowledge has two major dimensions, since, on the one hand, peer-to-peer communication is primarily intended to further research within specific disciplines, while, on the other, domain-external, asymmetric communication of 'filtered' knowledge caters to different types of lay-audiences. Collectively, the chapters in the volume take the reader on a journey through knowledge communication and knowledge (re)presentation strategies that are able to successfully disseminate and communicate. The domains under scrutiny are medicine and health, corporate communication, cultural heritage and tourism. A number of issues are addressed at the interface of corpus linguistics, genre studies and multimodal analysis. The variety of questions posed and methods used to explore corpus data will contribute to further debate among scholars in applied linguistics, sociolinguistics, multimodality, media studies and computer-mediated communication.